2020
DOI: 10.1371/journal.pone.0228314
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat stress on reference genes stability in heart and liver of two chickens genotypes

Abstract: Peer Review History: PLOS recognizes the benefits of transparency in the peer review process; therefore, we enable the publication of all of the content of peer review and author responses alongside final, published articles. The editorial history of this article is available here:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In addition, expression levels of Hprt1, Actb, and 18 s rRNA were significantly altered following acute HS on porcine iSCs. Although HS has been shown to influence reference gene stability in different chicken tissues (Cedraz de Oliveira et al, 2017; Gromboni et al, 2020), and in blood of Bama miniature pigs (Ju et al, 2011), suitable reference genes of porcine iSCs under acute HS have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, expression levels of Hprt1, Actb, and 18 s rRNA were significantly altered following acute HS on porcine iSCs. Although HS has been shown to influence reference gene stability in different chicken tissues (Cedraz de Oliveira et al, 2017; Gromboni et al, 2020), and in blood of Bama miniature pigs (Ju et al, 2011), suitable reference genes of porcine iSCs under acute HS have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported relatively high variability for the expression of WU-HKGs in a varied range of tissues and organs in livestock animals ( Gromboni et al, 2020 ; Lozano-Villegas et al, 2021 ) as well as in humans ( Mahoney et al, 2004 ; Caracausi et al, 2017 ; Cadenas et al, 2022 ), mice ( Fu et al, 2020 ; Muñoz et al, 2021 ), and insects ( Shi et al, 2016 ), among others.…”
Section: Resultsmentioning
confidence: 99%
“…On that account, only 33 WU-HKGs were analyzed. Gromboni et al (2020) assessed the suitability of eight HKGs for heart. Their studied WU-HKGs were present in neither the top 10 genes nor the list of 23 V-HKGs of heart tissue in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability rank order in the tissue groups was different from that observed in the acaricide treatment groups, with α‐tubulin and RpL5 being the most stable and Actin and eEF2 being the least stable. α‐tubulin encodes a major component of the cytoskeleton and has been widely accepted as a reference gene across various species (P. Liang et al, 2014; Rentoft et al, 2010; Sun et al, 2010) along with RpL5 , which encodes a ribosomal subunit protein (Gromboni et al, 2020; Hul et al, 2020). Both α‐tubulin and RpL5 showed good performance in all the cross‐tissue comparisons, except for the cuticle‐gut/fat body comparison, indicating that the application of both genes as reference genes for cross‐tissue comparison is reliable.…”
Section: Discussionmentioning
confidence: 99%